1970
DOI: 10.1530/jrf.0.0220549
|View full text |Cite
|
Sign up to set email alerts
|

Oviduct Secretion in the Cow

Abstract: Little is known regarding the physiological rôle of oviduct fluid on ova and spermatozoa in the reproductive tract. VanDemark (1958) and Bishop (1961) suggested that luminal fluids may be an important transport and nutrient medium for the gametes; others felt that oviduct secretions influenced sperm activity (Olds & VanDemark, 1957a) or aided the capacitation process (Austin, 1951: Chang, 1951. Oviduct fluid has been collected from several species by ligation of portions of the genital tract (Blandau, Jensen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
1

Year Published

1975
1975
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 10 publications
(12 reference statements)
4
32
1
1
Order By: Relevance
“…Carlson et al (1970) found protein concentrations of 0-083 and 0-158 g/100 ml in oviducal fluids from two cows, but Stanke et al (1974) reported values of 4-0 to 5-2 g/100 ml. In our studies, no significant variation in protein concentration of the secretion at different stages of the oestrous cycle was detected and this is in accord with the results of other workers (Restall & Wales, 1966;Perkins & Goode, 1966;Carlson et al, 1970;Stanke étal., 1974).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Carlson et al (1970) found protein concentrations of 0-083 and 0-158 g/100 ml in oviducal fluids from two cows, but Stanke et al (1974) reported values of 4-0 to 5-2 g/100 ml. In our studies, no significant variation in protein concentration of the secretion at different stages of the oestrous cycle was detected and this is in accord with the results of other workers (Restall & Wales, 1966;Perkins & Goode, 1966;Carlson et al, 1970;Stanke étal., 1974).…”
Section: Discussionmentioning
confidence: 92%
“…It is now well established that the volume of fluid secreted by the oviduct of ruminants undergoes a cyclic variation, maximum amounts being produced during oestrus and the volume decreasing to small amounts during the progestational phase (cow: Carlson et al, 1970;Stanke et al, 1974; sheep: Black, Duby & Riesen, 1963;Perkins, Goode, Wilder & Henson, 1965;Iritani, Gomes & VanDemark, 1969;Bellvé & McDonald, 1970 Perkins & Goode (1966) reported a mean value of 3-02 g/100 ml. Carlson et al (1970) found protein concentrations of 0-083 and 0-158 g/100 ml in oviducal fluids from two cows, but Stanke et al (1974) reported values of 4-0 to 5-2 g/100 ml.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fructose in the semen would have the same effect, thus inhibiting capacitation until the fructose had been diluted out in the cow's reproductive tract. Glucose inhibition of capacitation does not occur in the cow's oviduct because the glucose concentration in the oviductal lumen is only 50-100 µM (Carlson et al, 1970), a concentration at which the glycolysis rate is negligible. This example further supports the concept that it is the oviductal lumen of the female whose contents determine the metabolic pathway driving motility of mammalian sperm in vivo.…”
Section: Glycolysis and Capacitation: In Bull Sperm Sugar As Foementioning
confidence: 99%
“…Glucose also inhibited heparin-induced intracellular alkalinization. The concentrations of glucose in typical culture medium (5 mM) are much higher than those in the bovine oviduct, which contains less than 100 p, M (Carlson et al, 1970) so inhibition of capacitation by glucose is unlikely in vivo.…”
Section: Stimulation Of Mammalian Sperm Fertilizingmentioning
confidence: 99%